(untitled) (Ukrainian Journal of Ophthalmology, 2024)
Introduction. Combined drug treatment of primary open-angle glaucoma (POAG) with several types of antihypertensive drops from different pharmacological groups is performed to enhance the hypotensive effect in cases when monotherapy does not always reduce intraocular pressure (IOP) to a tolerance level. Рurpose. Evaluation of the effectiveness and tolerability of a fixed combination antihypertensive drug, Glaubrinza, in the treatment of patients with POAG. Methods. Depending on the treatment, 2 groups of patients were formed. The main group included 30 patients (60 eyes), who instilled the drug Glaubrinza, 1 drop 2 times a day. The comparison group consisted of 30 patients (60 eyes), whom the drug Simbrinza was instilled according to the same scheme as the drug Glaubrinza. All patients underwent a general ophthalmological examination and special research methods, including: computer static perimetry, pachymetry, and optical coherence tomography (OCT). The local and general tolerability of the drug was assessed within 10 days using a standard scale. Results. The effectiveness of the treatment in the main group was assessed as high in 85% and moderately high in 15% and averaged 3.8±0.1 points. The effectiveness of treatment in the comparison group was assessed as moderately high in 20% and high in 80% of patients and averaged 3.8±0.03 points. Conclusions. Glaubrinza is a highly effective drug for treating POAG and is not inferior in all studied parameters to the reference drug and is also economically accessible to all segments of the population.